Analysis of Single Nucleotide Polymorphisms on Locus 13q33.1-34 in Multigenerational Families of Cleft Lip Palate using MassArray - Praveen Kumar Neela; Srinivas Reddy Gosla; Akhter Husain; Vasavi Mohan; Sravya Thumoju; Rajeshwari Rajeshwari (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Cleft lip palate is a common congenital anomaly with multifactorial etiology. Many high-risk markers at different loci were reported to be involved in its etiology. Advanced genetic research led to the discovery of evidence of a new linkage on 13q33.1-34 region at marker rs1830756 in two multigenerational Indian families. However, no further study was reported to confirm or validate this linkage in other families. Hence, the present study was designed.METHODS: Twenty multigenerational families affected by non-syndromic cleft lip palate were selected for the study. Polymorphisms, rs1830756, rs1323672, rs1935135 of FAM155A gene; rs1961495, rs953386, rs1411040 of COL4A1 gene; and rs726449, rs984300 of MYO16 gene were selected. Genomic DNA was isolated and sent for genetic analysis by single nucleotide polymorphism (SNP) genotyping using the MassArray method. Statistical analysis of the genomic data was done by PLINK. Bonferroni correction was applied and haplotype analysis was done using Haploview software.RESULTS: Polymorphisms followed the Hardy Weinberg Equilibrium. In the allelic association, all the polymorphisms analysed showed no statistical significance. Hence, there was no significant difference in the allelic frequencies between non-syndromic cleft lip palate patients and healthy controls. The odds ratio was not more than 1.6 for all the SNPs. Haplotype analysis showed that haplotypes were not significantly higher in non-syndromic cleft patients than in control subjects.CONCLUSION: There is no association between SNPs analysed in the locus 13q33.1-34 with cleft lip palate.KEYWORDS: cleft lip palate, chromosome, polymorphism